Impact of teaching quality on student achievement: student evidence - Engida, Mengistu Anagaw; Iyasu, Ashagrie Sharew; Fentie, Yalemwork Mossu (Frontiers in Education, 2024)
Studies indicate that students who have access to highly qualified teachers achieve at a higher rate, regardless of other factors though the essence of quality teaching and teacher quality has not been adequately established. Nonetheless, three strands of teaching quality research focusing on observations via professional standards, value-added measures and student evaluations have been underway with recent developments favoring integrations. This study explores how the quality of mathematics and English language teachers is associated with students' achievement using a professional standard observation tool for student evaluation. A representative multistage sample of students and teachers selected from high schools in the East Gojjam Administrative Zone participated in the study. Using the domains in the Framework for Teaching (FfT) (Danielson, 2014)as indicators of teaching quality, the study identified the indicators that are associated with the academic achievement of students in mathematics and English subjects. Multiple linear regression analysis was used to study the relationships between the independent variables (teachers' quality indicators) and the dependent variable (students' grade 10 exam scores). Of the four domains of FfT, the delivery of instruction revealed a positive and significant association (sig= 016) with students' scores in the English language. The delivery of instruction encompasses communicating with students, using questioning and discussion techniques, and demonstrating flexibility and responsiveness, which are positively associated with students' scores in the English language. Conversely, managing classroom procedures was the only subdomain associated (sig=014) with an increase in students' mathematics scores. Accordingly, suggestions are made for research and practice.